Evaluation of designed pharmaceutical pictograms among the Malaysian population - Anil Tumkur; Pravinkumar Ingle; Quinnie Ling Sze Ning; Nurul Asikin Bustamin; Tee Kai Heng; Chai Tze Leen; Ketan Hatware (Clinical Epidemiology and Global Health, 2025)
Background: Poor medication adherence to treatment regimen and medication errors among patients are the main concerns for pharmacists. One creative way to make medical information easier to understand, improve health literacy, and be more memorable for patients is through simple, culturally relevant, and context-specific pharmaceutical pictograms. Objectives: This study evaluated the understanding of the population in the four regions of Malaysia regarding 22 designed Malaysian pictograms. Materials and methods: A cross-sectional study was conducted in 800 participants from the four different regions, with 200 participants from each region, using a convenience sampling method. Their interpretations of pictograms were classified and recorded. The correct recognition rate was used to determine whether each pictogram had met the ISO criterion of ≥66.7 % or the ANSI criterion of ≥85 %. Results: Seventeen pictograms met the ISO criteria of >67 %, while seven pictograms met the ANSI criteria of >85 % before the explanation was provided. After the explanation, all pictograms met the ISO criteria, but only two pictograms did not meet the ANSI criteria. There was a significant difference in interpretation performance before and after the explanations were given. Conclusion: The pictograms are suitable for introduction and can effectively convey medication-related information when used alongside verbal explanations and simple texts. This can improve communication and facilitate health education.